244 Pharmacokinetics of tulathromycin following administration with remote delivery devices. (7th December 2018) - Rivera, J; Tipton, P; Johnson, J; Woolums, A; Giguère, S; Lutz, A; Hice, I; Crosby, W; Thoresen, M
Abstract: Fifteen crossbred beef steers (BW = 302.5 + 21.7 kg) were used in a three way crossover design to determine the pharmacokinetics of tulathromycin (DRAX; Draxxin, Zoetis) following administration with remote delivery devices (RDD). Cattle were weighed, fitted with jugular catheters and assigned to one of three administration methods (2.5 mg of DRAX per kg of BW): subcutaneous injection of tulathromycin (SC), injection with an air pump RDD (AIR, Pneudart, Model 178B) at 4.5 m distance, and injection with a CO2 powered RDD at 7.5 m (CO, Pneudart, Model 176B). Blood was collected prior to injection and at various time points up to 552 h post administration and data were analyzed as a mixed model using animal as a random effect and method of administration, order of administration and their interaction as fixed effects. Three darts administered by AIR did not discharge (20%; 95% CI = 4% to 48%); and results from these steers were excluded from results. Maximum plasma concentration (718, 702.6, and 755.5 mg/mL for SC, AIR and CO, respectively) or the area under the concentration time (17, 885, 17, 423, and 18, 796 µg h/mL for SC, AIR and CO, respectively) were similar and not significantly ( P > 0.05) different between methods of administration. Results suggest that pharmacokinetics of DRAX following RDD are similar to subcutaneous injection; however failure of RDD darts to discharge can cause a proportion of cattle to fail to receive drug as expected.